Twice Neokoros : Ephesus, Asia, and the cult of the Flavian imperial family - Friesen, Steven J. (Religions in the Graeco-Roman World, 1993)
Twice Neokoros is a case study of the Cult of the Sebastoi that was established in the city of Ephesus by the province of Asia during the late first century C.E. Epigraphic and numismatic data indicate that the Cult of the Sebastoi was dedicated in 89/90 to the Flavian imperial family. The architecture, sculpture, municipal titles, and urban setting of the cult all reflect Asian religious traditions. The image of Ephesus was significantly altered by the use of these traditions in the institutions related to the Cult of the Sebastoi. Within the context of the history of provincial cults in the Roman Empire, the Cult of the Sebastoi became a turning point in the rhetoric of social order. Thus, the Cult of the Sebastoi served as a prototypical manifestation of socio-religious developments during the late first and early second century in the Eastern Mediterranean.